2016
DOI: 10.1556/650.2016.30615
|View full text |Cite
|
Sign up to set email alerts
|

A parlagfű okozta légzőszervi allergiás megbetegedések előfordulása Magyarországon

Abstract: Bevezetés: A szerzők a parlagfűallergiások számának becslésére a 18 év feletti lakosok körében végeztek országos, reprezentatív, kérdőíves felmérést. Célkitűzés: Az elsődleges cél a tünetekkel élő parlagfűallergiások felkutatása, a másodlagos cél a parlagfűallergiások tüneteinek, kivizsgálásának, gyógyszerfogyasztási szokásainak a feltérképezése volt. Módszer: A szerzők az általuk összeállított kérdőívvel 1000 lakost kerestek meg. A kérdőívek kitöltése és vissza küldése elektronikus úton történt. Eredmények: S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
2
1
1
Order By: Relevance
“…Thirty-one percent of their respondents have had allergic rhinitis, and 22% of the respondents experienced allergic rhinitis during “ragweed season” (between August and September). 24 Our results are comparable with these findings, as we detected a 25.5% prevalence of pollen hypersensitivity. However, in 2019, another survey was conducted in schoolchildren regarding allergic rhinitis in Budapest, the capital of Hungary, where the parent-reported prevalence of allergic rhinitis was found to be 29.3%, while only 9.7% of the children were diagnosed by a physician.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thirty-one percent of their respondents have had allergic rhinitis, and 22% of the respondents experienced allergic rhinitis during “ragweed season” (between August and September). 24 Our results are comparable with these findings, as we detected a 25.5% prevalence of pollen hypersensitivity. However, in 2019, another survey was conducted in schoolchildren regarding allergic rhinitis in Budapest, the capital of Hungary, where the parent-reported prevalence of allergic rhinitis was found to be 29.3%, while only 9.7% of the children were diagnosed by a physician.…”
Section: Discussionsupporting
confidence: 91%
“…However, in 2019, another survey was conducted in schoolchildren regarding allergic rhinitis in Budapest, the capital of Hungary, where the parent-reported prevalence of allergic rhinitis was found to be 29.3%, while only 9.7% of the children were diagnosed by a physician. 25 This suggests a higher perceived prevalence if we rely on questionnaires instead of clinical diagnoses, which can be true about our survey and that of Márk et al 24 as well.…”
Section: Discussionmentioning
confidence: 67%
“…A similar rate of association was also reported in previously published data [12,22,24,29]. Surprisingly, Mark et al [30] reported a lower rate of associated asthma in Hungary, but they did not distinguish between mono- or poly-sensitized patients. Patients with multiple sensitizations are exposed to allergens for longer, which may explain a persistent inflammation in both upper and lower airways and a higher rate of asthma association.…”
Section: Discussionsupporting
confidence: 86%
“…Other European countries with known allergy issues caused by A. artemisiifolia, such as Italy and Hungary (Bonini et al 2016, Márk et al 2016, also resulted in high hotspot densities in the current and future scenarios, although they reported a much lower percentage than the countries with the highest densities in the present study. Indeed, if one observes the spatial model in more detail, a high density of hotspots can be found in a few municipalities (e.g., Milan, Budapest, etc.…”
Section: Discussioncontrasting
confidence: 54%